Perfectives, imperfectives and the Croatian present tense - Geld, Renata (Array, 2007)
This paper attempts to re-examine the nature of the Croatian present tense in the light of the cognitive linguistic view of grammatical structure. In order to account for what Croatian traditional grammars describe as the usage of the present tense for the so-called ‘ non-real present’ , we will use the naive characterization approach suggested by Langacker (1991: 250). We will consider the following issues: tense as an epistemic category, the nature of perfective and imperfective processes (cf. e.g. Langacker 2001b) and the relevance of this classification of process types for aspectual phenomena in Croatian, as well as the role of extreme subjectification (Langacker 2003: 13) in the characterization of non-temporal uses of the Croatian present tense. Rather than hypothesizing distinct meanings for the present tense morpheme, we recognize the present tense morpheme as a consistent marker of proximity, indicating immediacy of the process in relation to the speaker. In doing so, we will discuss the high degree of subjectivity present in cases where the speaker describes ‘ virtual processes’ that occur as a result of her conceptualizing activity. Finally, we will demonstrate how general cognitive models proposed for examining the grammatical category of tense can yield situation-specific models that incorporate process types, as well as aspects of viewing arrangement. Having taken into consideration the nature of process types, the epistemic value of the present tense marker and specific departures from the canonical viewing arrangement (Langacker, 2003:18), we argue that non-temporal usages of the Croatian imperfective and perfective present are as ‘ real’ as their temporal usages, or more specifically, that, just like in English, their non-temporal or non-present uses can be accounted for in terms of the inherent value of indicating present time (cf. Langacker 2001b: 267).